Creeping into freedom: woman’s body in “The yellow wallpaper”, by Charlotte Perkins Gilman - Duarte, Leticia Rocha; Costa, Cynthia Beatrice (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2021)
Even though the short story “The Yellow Wallpaper” (1892), by Charlotte Perkins Gilman, has received much attention, especially from feminist literary criticism, there have been relatively few considerations on the main character’s body and on how it relates to her ordeal under patriarchal repression. By examining the physical aspect of the narrator’s experience, this article investigates two main hypotheses: (1) that the narrator’s body is controlled as a means of controlling her mind, but this fails when she uses her mind to free her body; and (2) that the “creeping” movement obsessively mentioned by the narrator can be interpreted as a subversion. This second proposition counterpoints the notion that the narrator’s descent into madness is proof of male triumph over female freedom.